Способы повышения эффективности многоканального фильтра доплеровского сигнала - Vasilevsky, V. V.; Golovan, V. G.; Drozdov, M. A.; Hyjnyak, T. A. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
The two ways of management of the peak-frequency characteristic of the Doppler multichannel filter for the purpose of combining its resection zone with a passive hindrance spectrum have been offered.